Emergency peripartum hysterectomy: a 7-year review at tertiary hospital - K., Manjula S.; Katakam, Suvarchala; G., Shobha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Emergency peripartum hysterectomy (EPH) is a major obstetric procedure, usually performed as a life-saving measure in cases of intractable obstetric hemorrhage. The aim of this study was to determine the incidence, indications and the risk factors and complications of emergency peripartum hysterectomy (EPH). The medical records of 13 patients who had undergone EPH, between January 2012 and December 2018, were reviewed retrospectively. All necessary data was obtained by record review. The mean age of pregnant women was 30 year. There were 13 EPHs out of 15768 deliveries, a rate of 0.82 per 1,000 deliveries. Out of 13 women who underwent EPHs, 8 hysterectomies were performed after cesarean delivery and 5 after vaginal delivery. The most common indication for hysterectomy was abnormal placentation (7/13), followed by atony (4/13), rupture of scared uterus (1/13) and rupture of unscared uterus (1/13). There were two cases of intra-operative bladder injury, we had 1/13 maternal death because of EPH. There were no cases of neonatal mortality. In our series, abnormal placentation was the most common of indication for EPH. The risk factors for EPH were previous CS for abnormal placentation and placental abruption for uterine atony and peripartum hemorrhage. Limiting the number of CS deliveries would bring a significant impact on decreasing the risk of EPH.